Speed meter for an endless band. - Gomez E., J.; Villanueva, D. (Revista Mexicana de Ingenieria Biomedica, 2018)
The test of effort that is made on an endless band to an individual is fundamental in sports medicine, the test consists of measuring the speed of race that reaches a subject in the endless band. A large number of the endless bands that currently exist in public and private institutions in the country, do not have a system that tells the doctor the exact speed. A system is proposed that shows in a luminous numerical display, the data is calculated from a series of pulses obtained from a photoelectronic sensor and processed by digital circuits.